Status of Geothermal Energy Exploration and Development in Uganda - Bahati, Godfrey; Tuhumwire, Joshua; Natukunda, James Francis (Department of Geological Survey and Mines, 2008)
Exploration for geothermal energy in Uganda has been in progress since 1993. The studies have focused on three major geothermal areas namely Katwe, Buranga and Kibiro. The three areas are in an advanced stage of surface exploration and will soon be subjected to exploratory drilling that will pave the way for a feasibility study. The overall objective of the study is to develop geothermal energy to complement hydro and other sources of power to meet the energy demand of rural areas in sound environment. The methodology of the study has focused on geology, geochemistry, hydrology and geophysics with the aim of elucidating subsurface temperatures and the spatial extent of the geothermal systems. The results indicate that the geothermal activity in the three areas is related to the volcanic and tectonic activities of the Rift Valley, which has a higher heat flow than the surrounding Precambrian crust. Subsurface temperatures of approximately 140-200˚C, 120-150˚C and 200-220˚C for Katwe, Buranga and Kibiro respectively have been predicted by geothermometry. Anomalous areas have been delineated in Katwe and Kibiro prospects using geophysical methods. Drilling of shallow boreholes to a depth of 200-300m for temperature gradient measurement has been completed and the temperatures measured (30-36˚C/km) are slightly above the global average of 30˚C/km. These results and proposed additional geophysical measurements will be used to update the geothermal models in three areas that will be a basis for the drilling of deep exploration wells. The results of the preliminary geothermal investigations of the other areas predict subsurface temperatures of 100 - 160˚C suitable for electricity production and direct uses. The areas have been graded based on predicted subsurface temperatures and other geothermal features for further exploration and development.